Dimensionamento de um edifício de seis pavimentos em alvenaria estrutural de blocos cerâmicos - Moraes, Eduardo Nervis (My University, 2018)
The growth of the competitiveness of the construction market generated a need to find for alternative construction systems that could combine economy, time and technical quality, and the structural masonry presents itself as a good solution to this problem. This work presents the project and dimensioning of a six-pavement residential building in structural masonry of ceramic blocks. The dimensioning was done using spreadsheets developed following the specifications of NBR 15812-1: 2010: Structural Masonry - Ceramic Blocks Part 1: Project. The main concepts and procedures performed for the building project are presented, as well as the results obtained. For the work, an existing architectural project was used as the basis for the beginning of the project and dimensioning. With this, the modulations were defined and the plants of first and second rows were developed, and from that, the steps of the dimensioning and structural analysis of the building began. Finally, the views and details of the walls of the building were made. After the calculations were made, it was verified the necessity of the use of reinforcement with structural function, with that the work`s hypothesis, that it was possible to execute the construction of six-pavement without the use of reinforcement, proved to be flawed, mainly due to the arrangement of the walls and frames of the architectural project employed (sic).
O crescimento da competitividade do mercado da construção civil gerou uma necessidade de procurar por sistemas construtivos alternativos que fossem capazes de juntar economia, prazo e qualidade técnica. A alvenaria estrutural se apresenta como uma boa solução para este problema. Este trabalho apresenta o projeto e dimensionamento de uma edificação residencial de seis pavimentos em alvenaria estrutural de blocos cerâmicos. O dimensionamento foi realizado por meio de planilhas desenvolvidas seguindo as especificações da NBR 15812-1:2010: Alvenaria Estrutural - Blocos cerâmicos Parte 1: Projeto. São apresentados os principais conceitos e procedimentos realizados para o projeto da edificação, bem como os resultados obtidos. Para o trabalho, foi utilizado um projeto arquitetônico já existente como base para o início do projeto e dimensionamento. Com este, definiu-se as modulações e foram desenvolvidas as plantas de primeira e segunda fiadas, e a partir disso, iniciaram-se as etapas do dimensionamento e análise estrutural da edificação. Por fim, foram realizadas as vistas e detalhamentos das paredes da edificação. Após a realização dos cálculos, foi verificada a necessidade do emprego de armadura com função estrutural, com isso a hipótese do trabalho, que era possível a execução da edificação de seis pavimentos sem o emprego de armadura de reforço, mostrou-se falha, principalmente devido ao arranjo das paredes e esquadrias do projeto arquitetônico empregado (sic).
Keywords: Construção civil; Alvenaria; Blocos (Materiais de construção); Projeto estrutural